Sex Differences in Long-Term Mortality After Stroke in INSTRUCT (INternational STRoke oUtComes sTudy): A Meta-Analysis of Individual Participant Data. (February 2017) - Phan, Hoang T.; Blizzard, Christopher L.; Reeves, Mathew J.; Thrift, Amanda G.; Cadilhac, Dominique; Sturm, Jonathan; Heeley, Emma; Otahal, Petr; Konstantinos, Vemmos; Anderson, Craig; Parmar, Priya; Krishnamurthi, Rita; et al.
Abstract : Background—: Women are reported to have greater mortality after stroke than men, but the reasons are uncertain. We examined sex differences in mortality at 1 and 5 years after stroke and identified factors contributing to these differences. Methods and Results—: Individual participant data for incident strokes were obtained from 13 population-based incidence studies conducted in Europe, Australasia, South America, and the Caribbean between 1987 and 2013. Data on sociodemographics, stroke-related factors, prestroke health, and 1- and 5-year survival were obtained. Poisson modeling was used to estimate the mortality rate ratio (MRR) for women compared with men at 1 year (13 studies) and 5 years (8 studies) after stroke. Study-specific adjusted MRRs were pooled to create a summary estimate using random-effects meta-analysis. Overall, 16 957 participants with first-ever stroke followed up at 1 year and 13 216 followed up to 5 years were included. Crude pooled mortality was greater for women than men at 1 year (MRR 1.35; 95% confidence interval, 1.24–1.47) and 5 years (MRR 1.24; 95% confidence interval, 1.12–1.38). However, these pooled sex differences were reversed after adjustment for confounding factors (1 year MRR, 0.81; 95% confidence interval, 0.72–0.92 and 5-year MRR, 0.76; 95% confidence interval, 0.65–0.89). Confounding factors included age, prestroke functional limitations, stroke severity, and history of atrial fibrillation. Conclusions—: Greater mortality in women is mostly because of age but also stroke severity, atrial fibrillation, and prestroke functional limitations. Lower survival after stroke among the elderly is inevitable, but there may be opportunities for intervention, including better access to evidence-based care for cardiovascular and general health. Abstract : Supplemental Digital Content is available in the text.